HEAVY METALS (Ni, Cu, Zn AND Cd) CONTENT IN SERUM OF RAT FED GREEN MUSSELS - Muhammad Yudhistira Azis; Suryo Gandasasmita; Agung Dhamar Syakti (Journal Omni-Akuatika, 2015)
Green mussel (Perna viridis) can playing role as bio-indicator or biomonitoring agent for heavy-metalcontaminations in the sea. In this research, the concentrations of four elements Ni, Cu, Zn and Cd in P. viridis and in the serum of rat which orally feed by P. viridis were determined by Atomic Absorption Spectrometry (AAS) following dry acid digestion. Parameter analysis was evaluated by determining confidence limit for the obtained results. The result showed that there was a sequence of heavy-metal content in green mussels sample and laboratory rats serum, such as Ni < Cd < Cu < Zn.Keywords: heavy metals, green mussels, laboratory rats serum, AAS